Psychosocial therapeutic approaches for high-functioning autistic adults - Schweizer, Tina; Endres, Dominique; Dziobek, Isabel; Tebartz van Elst, Ludger (Frontiers in Psychiatry, 2024)
Autism spectrum disorder (ASD) is characterized by impaired social interaction and communication skills, repetitive behaviors, restricted interests, and specific sensory processing. Particularly, adults with high-functioning ASD often remain unrecognized, presumably due to their high compensatory skills, but at the cost of high stress, which is often linked to anxiety and depression. This may further explain the significantly high suicide rates and reduced life expectancy among individuals with ASD. Thus, providing support to high-functioning autistic adults in managing core symptoms, as well as co-occurring anxiety and depression, appears essential. To date, only a limited number of evidence-based psychosocial therapeutic options are available, and very few of them have undergone rigorous evaluation in a clinical context. To obtain a comprehensive understanding, a systematic literature search was conducted according to the PRISMA checklist, and only studies demonstrating robust methodological quality were included and discussed in this review article. Although promising initial key factors and methods have been identified, additional evidence-based studies are imperative to ascertain the optimal treatment and evaluate the long-term outcomes for adults with high-functioning ASD.